Clinicopathologic Characterization of GREB1-rearranged Uterine Sarcomas With Variable Sex-Cord Differentiation. (July 2019) - Lee, Cheng-Han; Kao, Yu-Chien; Lee, Wan-Ru; Hsiao, Yi-Wen; Lu, Tzu-Pin; Chu, Chia-Ying; Lin, Yi-Jia; Huang, Hsuan-Ying; Hsieh, Tsung-Han; Liu, Yun-Ru; Liang, Cher-Wei; Chen, Tom Wei-Wu; et al.
Abstract : Uterine mesenchymal tumors are genetically heterogenous; those with uniform cytomorphology, best exemplified by endometrial stromal tumors, often contain various fusion genes. Novel fusions involving ESR1 and GREB1, key factors in sex hormone pathways, have been implicated in rare uterine mesenchymal tumors. Particularly, the fusions between 5′- ESR1/GREB1 and 3′- NCOA2/NCOA3 were recently identified in 4 uterine tumors resembling ovarian sex-cord tumor (UTROSCT). By RNA sequencing, pathology review, and FISH screening, we identified 4 uterine sarcomas harboring rearranged GREB1, including GREB1-NCOA2 and the novel GREB1-NR4A3, GREB1-SS18, and GREB1-NCOA1, validated by RT-PCR and/or FISH. They occurred in the myometrium of postmenopausal women and were pathologically similar despite minor differences. Tumor cells were generally uniform and epithelioid, with vesicular nuclei and distinct to prominent nucleoli. Growth patterns included solid sheets, trabeculae/cords, nests, and fascicles. Only 1 tumor showed small foci of definitive sex-cord components featuring well-formed tubules, retiform structures, Leydig-like cells, and lipid-laden cells and exhibiting convincing immunoreactivity to sex-cord markers (calretinin, α-inhibin, and Melan-A). In contrast, all the 4 classic UTROSCT we collected occurred in premenopausal patients, consisted predominantly of unequivocal sex-cord elements, prominently expressed multiple sex-cord markers, and harbored ESR1-NCOA3 fusion. Combined with previously reported cases, GREB1 -rearranged tumors involved significantly older women ( P =0.001), tended to be larger and more mitotically active, showed more variable and often inconspicuous sex-cord differentiation, and appeared to behave more aggressively than ESR1 -rearranged UTROSCT. Therefore, these 2 groups of tumors might deserve separate consideration, despite some overlapping features and the possibility of belonging to the same disease spectrum. Abstract : Supplemental Digital Content is available in the text.